Spatiotemporal Properties of Neuron Response Suppression in Owl Monkey Primary Somatosensory Cortex When Stimuli Are Presented to Both Hands - Reed, Jamie L. (Society for Neuroscience, 2011)
Despite the lack of ipsilateral receptive fields (RFs) for neurons in the hand representation of area 3b of primary somatosensory cortex, interhemispheric interactions have been reported to varying degrees. We investigated spatiotemporal properties of these interactions to determine the following: response types, timing between stimuli to evoke the strongest bimanual interactions, topographical distribution of effects, and their dependence on similarity of stimulus locations on the two hands. We analyzed response magnitudes and latencies of single neurons and multineuron clusters recorded from 100-electrode arrays implanted in one hemisphere of each of two anesthetized owl monkeys. Skin indentations were delivered to the two hands simultaneously and asynchronously at mirror locations (matched sites on each hand) and nonmirror locations. Since multiple neurons were recorded simultaneously, stimuli on the contralateral hand could be within or outside of the classical RFs of any given neuron. For most neurons, stimulation on the ipsilateral hand suppressed responses to stimuli on the contralateral hand. Maximum suppression occurred when the ipsilateral stimulus was presented 100 ms before the contralateral stimulus onset (p < 0.0005). The longest stimulus onset delay tested (500 ms) allowed contralateral responses to recover to control levels (p = 0.428). Stimulation on mirror digits did not differ from stimulation on nonmirror locations (p = 1.000). These results indicate that interhemispheric interactions are common in area 3b, somewhat topographically diffuse, and maximal when the suppressing ipsilateral stimulus precedes the contralateral stimulus. Our findings point to a neurophysiological basis for “interference” effects found in human psychophysical studies of bimanual stimulation.